Stress-induced cardiac autonomic reactivity and preclinical atherosclerosis: does arterial elasticity modify the association?. (2nd November 2015) - Chumaeva, Nadja; Hintsanen, Mirka; Pulkki-Råback, Laura; Merjonen, Päivi; Elovainio, Marko; Hintsa, Taina; Juonala, Markus; Kähönen, Mika; Raitakari, Olli T.; Keltikangas-Järvinen, Liisa
Abstract: The effect of acute mental stress on atherosclerosis can be estimated using arterial elasticity measured by carotid artery distensibility (Cdist). We examined the interactive effect of acute stress-induced cardiac reactivity and Cdist to preclinical atherosclerosis assessed by carotid intima-media thickness (IMT) in 58 healthy adults aged 24–39 years participated in the epidemiological Young Finns Study. Cdist and IMT were measured ultrasonographically. Impedance electrocardiography was used to measure acute mental stress-induced cardiac autonomic responses: heart rate (HR), respiratory sinus arrhythmia and pre-ejection period after the mental arithmetic and the public speaking tasks. Interactions between HR reactivity and Cdist in relation to preclinical atherosclerosis were found. The results imply that elevated HR reactivity to acute mental stress is related to less atherosclerosis among healthy participants with higher arterial elasticity. Possibly, increased cardiac reactivity in response to challenging tasks is an adaptive reaction related to better cardiovascular health.